2017
DOI: 10.1142/s1363919617500013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alliance Portfolio Diversity on Innovation Performance: A Study of Partner and Alliance Characteristics in the Bio-Pharmaceutical Industry

Abstract: This study investigates the effects of alliance portfolio diversity on the innovation performance of firms. Alliance portfolio diversity is defined using partner characteristics (partner industrial background) and alliance characteristics (alliance objective). We also investigate the interaction between these two measures of diversity on innovation performance. The hypotheses are tested on a dataset of R&D alliances in the US biopharmaceutical industry from 1998–2002. We find an inverted U-shape relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…Phelps [65] demonstrated that technological diversity of a firm's alliance partners increases its exploratory innovation. In a similar vein, Marhold, Kim and Kang [64] found an inverted U-shape relationship between the diversity of alliance partners' industrial background and innovation performance, and a negative interaction of partner diversity and the diversity of the alliance objectives. Subramanian & Soh [76] explored the configuration of an alliance portfolio that links to recombinant innovation and showed that the technological diversity of a firm's alliance portfolio has a positive impact on the breadth of recombinant innovation produced by the firm.…”
Section: Alliance Portfoliosmentioning
confidence: 74%
See 2 more Smart Citations
“…Phelps [65] demonstrated that technological diversity of a firm's alliance partners increases its exploratory innovation. In a similar vein, Marhold, Kim and Kang [64] found an inverted U-shape relationship between the diversity of alliance partners' industrial background and innovation performance, and a negative interaction of partner diversity and the diversity of the alliance objectives. Subramanian & Soh [76] explored the configuration of an alliance portfolio that links to recombinant innovation and showed that the technological diversity of a firm's alliance portfolio has a positive impact on the breadth of recombinant innovation produced by the firm.…”
Section: Alliance Portfoliosmentioning
confidence: 74%
“…Moving from the dyadic to the network level can sensitize managers to the importance of understanding how social structure influences firm performance [62]. Within a relatively well-developed research strand devoted to alliance portfolios has first of all addressed the role of diversity in networks of innovation cooperation [63][64][65]. Zouaghi, Garcia & Garcia [63] explored the value of diversity in cooperation networks on innovation performance, finding a curvilinear relationship in line with other studies, suggesting that companies collaborating with different external partners show higher innovation performance, but only up to a certain point.…”
Section: Alliance Portfoliosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, diversity implies complexity, and therefore, significant management challenges in terms of coordination and interorganizational learning capabilities (Marhold et al, 2017). This is especially true in technologically intense industries, in which diverse partners may have competencies in very different knowledge and technological fields, as well as different perspectives and cultures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A diverse alliance portfolio prevents firms from being locked into their internal resource base by providing access to new and different kinds of resources from external sources, which in turn supports innovation (Marhold et al, ; Wuyts et al, ). Such argumentation is in line with one basic rationale of social network theory, which postulates a causal link between the network structure of a focal firm and its performance (Borgatti and Foster, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%